Diagnostic Accuracy of Tympanogram in Pediatric patients with Otitis Media with Effusion Taking Myringotomy findings As Gold Standard - Umera Iftikhar, Deepak Rai, Usman Aslam, Syed Noman Liaqat (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the diagnostic accuracy of tympanogram for diagnosis of otitis media with effusion in patients with conductive hearing loss. Study design: Cross-sectional study Setting: Department of ENT, Benazir Bhutto Hospital Rawalpindi. Duration of study with dates: The study was carried out over six months from 24-05-2018 to 23-11-2018. Methods: The study was conducted on 150 patients. Clinical examination of all patients was done for OME, then tympanograms were recorded and all patients underwent myringotomy. OME on tympanogram and myringotomy was recorded. Results: The average age of the patients was 6.4±2.0 years. The study included 76 males (50.7%) and 74 females (49.3%). The averagelengthof disease (OME) is 18.5±10.3 months. Diagnostic accuracy of tympanogram findings taking myringotomy as the gold standard showeda sensitivity of 99.2%, specificity of 70%, a positive predictive value of 97.8%, a negative predictive value of 87.5% and an accuracy of 97.3%. Stratification with regard to age, gender and duration of disease was also carried out. This study will help to start early medication and may help us to minimize the number of surgeries for OME i.e. myringotomy. Conclusion: In conclusion, OME was frequent in the age group 6-12 years. OME in children aged 2-12 years can be diagnosed using tympanometry more accurately. However, clinical findings and other supportive audiological tests are necessary for the ultimate decision regarding the treatment of such children as chances of false positive results exist. Keywords: Middle Ear ventilation; Tympanometry; Otitis Media With Effusion